KINERJA MS-222 DAN KEPADATAN IKAN BOTIA (Botia macracanthus) YANG BERBEDA SELAMA TRANSPORTASI - Yanto, Hendry; Raharjo, Eka I (Jurnal Perikanan dan Kelautan, 2009)
The research was aimed to find the optimal level of tricainemethanesulfonate (MS-222) and density of clown loach (Botia macracanthus) intransportation. These triplicate factorial experiments consisted of the three levelsof MS-222 (0, 25, and 50 ppm) and three densities of fish (25, 50 and 75 fish L-1).The fingerlings of clown loach (3.0-3.5 cm) have been transported in 1 liter ofwater for 18 hours. The results showed that the levels of MS-222, density of fishesand interaction of the both factors were different significantly (P<0.05) to theinduction time, sedative duration, and survival live of clown loach. Theinteraction level of MS-222 50 ppm with density 25 fishes L-1 was not significant(P>0.05) with 50 fishes L-1. Level of MS-222 50 ppm and density 50 fishes L-1were the best for survival live in transportation of clown loach.